Characterization of the Gut Microbiota of Individuals at Different T2D Stages Reveals a Complex Relationship with the Host - Alejandra Chávez-Carbajal; María Luisa Pizano-Zárate; Fernando Hernández-Quiroz; Guillermo Ortiz-Luna; Rosa María Morales‐Hernández; Amapola De Sales-Millán; María Hernández‐Trejo; Angelina García-Vite; Luis Beltrán-Lagunés; Carlos Hoyo‐Vadillo; Jaime Garcı́a-Mena (2020)
In this work, we studied 217 Mexican subjects divided into six groups with different stages of glucose intolerance: 76 Controls (CO), 54 prediabetes (PRE), 14 T2D no medication (T2D−No−M), 14 T2D with Metformin (T2D−M), 22 T2D with polypharmacy (T2D−P), and 37 T2D with polypharmacy and insulin (T2D−P+I). We aimed to determine differences in the gut microbiota diversity for each condition. At the phylum level, we found that Firmicutes and Bacteroidetes outline major changes in the gut microbiota. The gut bacterial richness and diversity of individuals in the T2D−No−M group were lesser than other groups. Interestingly, we found a significant difference in the beta diversity of the gut microbiota among all groups. Higher abundance was found for Comamonadaceae in PRE, and Sutterella spp. in T2D−No−M. In addition, we found associations of specific microbial taxa with clinical parameters. Finally, we report predicted metabolic pathways of gut microbiota linked to T2D−M and PRE conditions. Collectively, these results indicate that each group has specific predicted metabolic characteristics and gut bacteria populations for each phenotype. The results of this study could be used to define strategies to modulate gut microbiota through noninvasive treatments, such as dietary intervention, probiotics or prebiotics, and to improve glucose tolerance of individuals with prediabetes or T2D.